Soil phosphorus changes in a grey desert soil in Xinjiang, China, using 31P nuclear magnetic resonance spectroscopy. (October 2019) - Wang, B; Zhang, X; Fu, H; Liu, H; Wang, X H; Ma, Y B
Abstract: This study investigated the effects of different long-term fertilization regimes on the total phosphorus (TP) content and the phosphorus (P) composition of grey desert soil in Xinjiang, China, and clarified the variation in P content under different long-term fertilization regimes. Solution 31 P nuclear magnetic resonance spectroscopy ( 31 P NMR) was used to analyze the variation in TP and P composition under different long-term fertilization regimes. The results showed that phosphate monoester was the major form of P and that no other forms of soil organic P (OP) were detected in grey desert soil, Xinjiang, China.